Caveolin-1 expression predicts favourable outcome and correlates with PDGFRA mutations in gastrointestinal stromal tumours (GISTs). Issue 12 (21st June 2021) - Bertero, Luca; Gambella, Alessandro; Barreca, Antonella; Osella-Abate, Simona; Chiusa, Luigi; Francia di Celle, Paola; Lista, Patrizia; Papotti, Mauro; Cassoni, Paola
Abstract : Aims: Novel prognostic markers are warranted for gastrointestinal stromal tumours. Caveolin-1 is a multifunctional protein that proved to be associated with outcome in multiple tumour types. Aim of this study was to investigate Caveolin-1 expression and prognostic efficacy in a series of gastrointestinal stromal tumours. Methods: Caveolin-1 expression was assessed by immunohistochemistry in a retrospective series of 66 gastrointestinal stromal tumours representative of the different molecular subtypes. Correlations with clinical, histopathological and molecular features were investigated. Statistical analyses were performed as appropriate. Results: Thirty-five cases out of 66 (53.0%) expressed Caveolin-1. Presence of Caveolin-1 expression correlated with favourable histopathologic and clinical traits, including a lower mitotic count (p=0.003) and lower relapse rate (p=0.005). Caveolin-1 expression also resulted associated with the presence of PDGFRA mutations (p=0.010). Outcome analyses showed a favourable prognostic significance of Caveolin-1 expression in terms of relapse-free survival (HR=0.14; 95% CI=0.03 to 0.63) and overall survival (HR=0.29; 95% CI=0.11 to 0.74), even after adjusting for the mutational subgroup (relapse-free survival: HR=0.14, 95% CI=0.04 to 0.44; overall survival: HR=0.29, 95% CI=0.11 to 0.51) and imatinib treatment (relapse-free survival: HR=0.14, 95% CI=0.02 to 0.81; overall survival: HR=0.29, 95% CI=0.17 to 0.48). Conclusion: Caveolin-1 represents a novel prognostic marker in gastrointestinal stromal tumours. Further studies are warranted to validate these results and to explore the mechanisms linking Caveolin-1 expression with the PDGFRA oncogenic pathway.